Wireless at the “Connected Games”: How the London 2012 Olympic and Paralympic Games Utilized the Latest Wi-Fi Technology - Peter Leonhardt (Journal of Telecommunications and Information Technology, 2013)
The London 2012 Olympic and Paraolympic Games drew together tens of thousands of people in the form of athletes, organisers, media, VIPs, public and many more groups and individuals. With the growth in smart phones and tablets coupled with the ever expanding volume and range of content accessed via Aps and browsers, this huge volume of people expected connectivity from their mobile devices during their time on the Olympic sites. It was BT’s role in the games as the official communications services partner to deliver Wi-Fi connectivity across the venues, covering the range of users from the public, athletes, organisers and ticket scanners. This paper examines this state of the art Wi-Fi solution.